HUBUNGAN ANTARA TIPE KEPRIBADIAN EKSTROVERT DENGAN KECENDERUNGAN CYBERBULLYING PADA REMAJA AWAL PENGGUNA MEDIA SOSIAL INSTAGRAM - IGAA. Noviekayati; Nindia Pratitis; Dewi Atika Maisarah (Fakultas Psikologi Universitas Hang Tuah, 2018)
This research is conducted by teenagers who do cyberbullying, with the aim to know the relationship between personality type with cyberbullying tendency. This research was conducted at SMP Untag Surabaya with 118 subjects with early teens characteristic which have age range about 12-15 years old, have Instagram account and live in Surabaya city. Methods of data retrieval using the scale of Extrovert Personality Type and Cyberbullying Tendency. Both scales were prepared by researchers with Likert model. The technique used in this research is Nonparametric Statistics in the form of correlation. Based on calculation SPSS version 20.0 obtained result (r = - 0,059) with significance value (p = 0,524). Since the level of significance gained is greater than 0.05 (p is less than 0.05), it means that there is no equivalent to variable cyberbullying tendency, there is no positive relationship between extrovert personality type and cyberbullying tendency.